Implementation of Socio-Cultural Ergonomic Oriented Meklemiji Local Wisdom to Improve Health Quality and Community Care Attitude to Saving Water Resources - Ni Luh Putu Mia Lestari Devi; Anak Agung Ketut Sri Wiraswati; Ni Putu Sri Arnita; Edelina Leandro Maranresy (International Journal Labs, 2026)
Water resources in Sading Village are starting to experience a crisis due to the many land conversions. The majority of people in Sading Village have their own businesses which are generally done at home. The purpose of this study is to apply and prove that the implementation of local wisdom meklemiji oriented towards socio-cultural ergonomics through a participatory approach with socio-cultural ergonomic training combined with the provision of awareness programs can improve the quality of health and community concern for water resource rescue strategies. Experimental method with quasi-experimental research type with the same subject design (treatment by subject design) and randomized posttest only group design pattern, the assessment is carried out by conducting an assessment in the form of: (a) work stress questionnaire to determine indicators of work stress; (b) the rocksport method is used to record fitness indicators; and (c) a water resource rescue strategy questionnaire to determine indicators of community concern. The results of the study indicate that the implementation of local wisdom meklemiji oriented towards socio-cultural ergonomics improves the quality of public health as seen from the decrease in work-related stress by 32.02%, the increase in community fitness by 20.20%, and (c) increasing the community's caring attitude towards water resource rescue strategies by 35.95%. The conclusion of this study is that the implementation of local wisdom meklemiji oriented towards socio-cultural ergonomics improves the quality of health and community's caring attitude towards water resource rescue.